FAKTOR–FAKTOR YANG BERPENGARUH TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR DI BEI - Filicia Devina Kurniawan; Debora Debora (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2022)
The purpose of this study was to obtain empirical evidence about the factors that affect earnings management in manufacturing companies. The independent variables used in this study are Firm Size, Audit committee, Leverage, Independent Board of Commissioners, Return On Asset, Managerial Ownership, and Institutional Ownership. The sample obtained in this study used manufacturing companies listed on the Indonesia Stock Exchange (IDX) for 3 years in the period 2017 - 2019. There are 38 companies that meet the criteria by using purposive sampling method and multiple regression analysis for hypothesis testing. The results show that the variables of Firm Size, Audit Committee, Leverage, Independent Board of Commissioners, Retun On Asset, Managerial Ownership, and Institutional Ownership have no effect on earnings management.